WORK ENVIRONMENT AND EMPLOYEE PERFORMANCE: A DYADIC STUDY IN A STATE-OWNED TECHNICAL UNIT - Gustiawan, Willson; Syofyan, Raihana Mardhiyyah; Chandra, Benny (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2025)
Employee performance remains a critical determinant of organizational success, particularly in operational units of state-owned enterprises where efficiency and precision are essential. Among the many influencing factors, the work environment—both physical and non-physical—has drawn increasing attention as a strategic element of human resource development. This study aims to examine the relationship between work environment and employee performance at PT Kereta Api Indonesia (Persero) Divisi Regional II Sumatera Barat, focusing on UPT Balai Yasa Padang as a technical operations unit. Using a quantitative approach and a dyadic data collection method, the study involved 32 respondents through saturated sampling. Employees assessed their work environment, while supervisors evaluated employee performance, thereby minimizing common method bias. Data were collected via structured questionnaires adapted from validated instruments and analyzed using Spearman Rank Correlation. The findings reveal a moderate yet statistically significant positive correlation (rs = 0.482, p = 0.005) between the perceived quality of the work environment and employee performance. These results emphasize the importance of ergonomic, communicative, and psychologically safe work conditions in shaping productivity and accountability. Methodologically, the study contributes to organizational research by demonstrating the value of role-based dyadic assessments. The conclusion underscores the need for integrated environmental and supervisory improvements as part of performance management strategies in operationally intensive sectors.